2011
DOI: 10.1080/1062936x.2011.623324
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-based QSAR study for a series of 3,3-disubstituted-5-aryl oxindoles and 6-aryl benzimidazol-2-ones derivatives as progesterone receptor inhibitors

Abstract: Receptor-based comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) were performed on a series of 54 progesterone receptor (PR) inhibitors. The established CoMFA model from the training set gives statistically significant results with the cross-validated q (2) of 0.534 and non-cross-validated [Formula: see text] of 0.947. The best CoMSIA model was derived by the combination of steric field and hydrophobic field with a q (2) of 0.615 and [Formula: see text]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Figure 3(a) (using Surflex-Dock). The docking results showed that four H-bonds are formed between the ligand (14) and protein (hDHODH). The carboxylic acid group in Compound 14 formed H-bonds with Arg136 and Gln47, which have already been found to be important residues for binding the ligand to the active site and also for providing inhibition.…”
Section: In Silico Admet Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3(a) (using Surflex-Dock). The docking results showed that four H-bonds are formed between the ligand (14) and protein (hDHODH). The carboxylic acid group in Compound 14 formed H-bonds with Arg136 and Gln47, which have already been found to be important residues for binding the ligand to the active site and also for providing inhibition.…”
Section: In Silico Admet Studiesmentioning
confidence: 99%
“…In CoMSIA similarity indices are calculated at regularly placed grid points for aligned molecules. CoMSIA calculates other molecular descriptors, such as hydrophobic fields, and H-bond donor and acceptor fields [13,14].…”
Section: Introductionmentioning
confidence: 99%